2020
DOI: 10.3389/fbioe.2020.00919
|View full text |Cite
|
Sign up to set email alerts
|

Bases for Treating Skin Aging With Artificial Mitochondrial Transfer/Transplant (AMT/T)

Abstract: The perception of mitochondria as only the powerhouse of the cell has dramatically changed in the last decade. It is now accepted that in addition to being essential intracellularly, mitochondria can promote cellular repair when transferred from healthy to damaged cells. The artificial mitochondria transfer/transplant (AMT/T) group of techniques emulate this naturally occurring process and have been used to develop therapies to treat a range of diseases including cardiac and neurodegenerative. Mitochondria acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 160 publications
(262 reference statements)
0
14
0
Order By: Relevance
“…Considering that increased OS contributes to skin senescence [ 3 , 43 ], it is expected that skin anti-ageing products containing antioxidants would reduce the harmful effects of free radicals and minimize the consequences of skin aging. However, limitations exist for most conventional antioxidants [ 21 ]. Moreover, if antioxidants do not directly target mitochondria, their protective efficacy in that organelle is compromised [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that increased OS contributes to skin senescence [ 3 , 43 ], it is expected that skin anti-ageing products containing antioxidants would reduce the harmful effects of free radicals and minimize the consequences of skin aging. However, limitations exist for most conventional antioxidants [ 21 ]. Moreover, if antioxidants do not directly target mitochondria, their protective efficacy in that organelle is compromised [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, limitations exist for most conventional antioxidants [ 21 ]. Moreover, if antioxidants do not directly target mitochondria, their protective efficacy in that organelle is compromised [ 20 , 21 ]. For this reason, targeting mitochondria with antioxidants can be looked as a rational strategy to delay skin ageing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of reduced energy production, there are interrelated steps of Caspase activation, membrane depolarization, and cytochrome C release from mitochondria. These processes affect various cellular processes such as cell migration and cell division, also lead to increased mitochondrial oxidative stress levels because of a many-fold increase in ROS production at mitochondrial complexes [ 117 , 118 ]. Enzyme Endogenous antioxidant system of mitochondria, including glucose-6-phosphate dehydrogenase, thioredoxin reductase, glutathione–S-transferases, and peroxidase, is their best defense system against increased levels of ROS.…”
Section: The Pathological Mechanisms Of Skin Photoagingmentioning
confidence: 99%
“…Furthermore, during aging mitochondria DNA mutations cumulate and respiratory function declines (Wei et al 2009 ). Mitochondria functionality is so crucial for skin health during aging that some authors suggested very recently an artificial mitochondria transfer/transplant (AMT/T) to promote renewal of senescent skin cells, even revitalizing them (Balcázar et al 2020 ).…”
Section: -Lactate Ros and Mitochondria: Role In Skin Agingmentioning
confidence: 99%